THE IMPORTANT ROLE OF ORAL MEDICINE SPECIALIST IN MANAGEMENT OF STEVENS-JOHNSON SYNDROME PATIENT - Nuri Fitriasari; Eko Rotary Nurtito; Nanan Nur’aeny; Indah Suasani Wahyuni (FKG Unlam, 2020)
ABSTRACTIntroduction: Stevens-Johnson Syndrome (SJS) is an acute hypersensitivity reaction that manifests on the skin, oral mucosa, ocular, gastrointestinal, genital and anal area. It is also potentially life-threatening in concern of dehydration and infection. Oral mucosal lesions due to SJS resulted in a significant decrease of patient’s quality of life. When the oral mucosa involved, the intake of nutrients and fluids is disrupted contributing to electrolyte imbalance that aggravates dehydration. Moreover, oral mucosal lesions have become an entry point for infection. Purpose: This case report describes the important role of oral medicine specialists in the management of oral mucosal lesions in SJS patient. Review: A 26-year-old female patient was referred from the Department of Dermatology and Venereology with a diagnosis of SJS et causa suspected paracetamol and/or amoxycillin. The complaints comprised of pain on the lips and oral cavity, difficulty in mouth opening, and pain when swallowing. The management for oral lesions included: history taking, external and intra oral examinations, dexamethasone mouthwash, nystatin oral suspension, and sodium chloride (NaCl) 0.9% solution. The patient showed improvement in oral mucosal lesions within 3 weeks of treatment that was provided by oral medicine specialist and medical team collaboration. Conclusion: Based on this case report, the role of oral medicine specialist is very important as part of the management team for SJS patient. Oral medicine specialist can reduce morbidity that results from oral mucosal involvement. Collaboration with oral medicine specialist since the beginning of treatment is the key to success in SJS management. Keywords: Oral medicine specialist, Oral mucosal lesion, Stevens-Johnson Syndrome.